Permeable concrete pavement elaborated with civil construction residue - Caroline Godoy de Souza, Bruna; Paula Moreno Trigo Gregui, Ana (Seven Editora, 2023)
Currently, with urban expansion, there are two major issues of concern: soil sealing and the generation of civil construction waste (RCC). Soil compaction and asphalting make it difficult for water to infiltrate, which can lead to flooding in lower areas. The waste generated, when disposed of irregularly, causes obstruction of roads, the proliferation of vectors, silting of streams and rivers, etc. The use of permeable concrete pavements made with RCC aggregates is an innovative and sustainable solution to this problem. Therefore, this research proposes to incorporate recycled aggregates in the production of structural concrete, for later application in permeable pavements. 2 m 2 of permeable pavement were built, 1 m 2 made with blocks containing RCC, and 1 m 2 with blocks containing natural aggregate. The performance of the pavements was verified through tests of compressive strength and permeability, showing the positive interference of the construction residue in the pavement drainage. DOI: 10.56238/pacfdnsv1-070